Compact modulators on silicon nitride waveguide platform via micro-transfer printing of thin-film lithium niobate - S. Hadi Badri; Maria V. Kotlyar; Risov Das; Yeasir Arafat; Owen Moynihan; Brian Corbett; Liam O’Faolain; Samir Ghosh (Scientific Reports)
Abstract We explore the use of micro-transfer printing (µTP) technology to integrate thin lithium niobate (LN) films onto silicon nitride (SiN) waveguides, facilitating the development of compact electro-optical modulators. Three modulator architectures are investigated: Mach-Zehnder interferometer (MZI), Fabry-Perot (FP) resonator, and side-coupled FP resonators. By acting as a photonic molecule, the proposed coupled FP resonators enable improved spectral engineering with new functionalities while maximizing the transmission and quality-factor (Q-factor) of the resonances. Design, simulations, fabrication method, and experimental results are presented, demonstrating the potential of µTP in advancing electro-optical modulators. The half-wave voltage-length product (V π L) of the fabricated devices decreases as the Q-factor increases achieving V π L = 10.5, 4.3, and 2.74 V.cm for MZI, FP, and photonic molecule modulators, respectively.